UPAYA NON PENAL BHABINKAMTIBMAS POLSEK PARIAMAN TIMUR DALAM PENCEGAHAN TINDAK PIDANA KORUPSI DANA DESA - Afdhal Bustami (UNES Law Review, 2020)
Non-Penal Efforts by Bhabinkamtibmas of the East Pariaman Police in Preventing Corruption Crime Funds are to supervise the use of village funds in their respective regions. Bhabinkamtibmas supervises and monitors village funds using a direct supervision approach by assisting, monitoring and supervising the implementation of village development activities. The effort made is by delivering it at the mosque. Bhabinkamtibmas conveyed about village funds, namely about their use and forms of corruption that can occur in the management of village funds. Carry out activities of the residents' sambang and activities of using village funds. Legal Counseling at Village Offices / Community Figures Houses. This effort takes the form of face-to-face coordination with village fund management officers directly. Constraints faced include the low understanding of the duties and responsibilities of Bhabinkamtibmas members in carrying out tasks in the field, especially in understanding the implementation of tasks in building partnerships (Patnership Building) through a formality Polmas approach without any feedback from the community.